Prosecutors, voters, and the criminalization of corruption in Latin America : the case of Lava Jato / Ezequiel A. Gonzalez-Ocantos, Paula Muñoz Chirinos, Nara Pavão, Viviana Baraybar Hidalgo. - González Ocantos, Ezequiel; Muñoz Chirinos, Paula, 1977-; Pavão, Nara; Baraybar Hidalgo, Viviana (Cambridge studies in law and society., 2023)
Lava Jato, a transnational bribery case that started in Brazil and spread throughout Latin America, upended elections and collapsed governments. Why did the investigation gain momentum in some countries but not others? The book traces reforms that enhanced prosecutors' capacity to combat white-collar crime and shows that Lava Jato became a full-blown anti-corruption crusade where reforms were coupled with the creation of aggressive taskforces. For some, prosecutors' unconventional methods were necessary and justified. Others saw dangerous affronts to due process and democracy. Given these controversies, how did voters react to a once-in-a-generation attempt to clean politics? Can prosecutors trigger hope, conveying a message of possible regeneration? Or does aggressive prosecution erode the tacit consensus around the merits of anti-corruption? Prosecutors, Voters and The Criminalization of Corruption in Latin America is a study of the impact of accountability through criminalization, one that dissects the drivers and dilemmas of resolute transparency efforts.